Relationship of oil seep in Kudat Peninsula with surrounding rocks based on geochemical analysis - Azman, N.I. (Institute of Physics Publishing, 2017)
This study aims to investigate the relation of oil seepage at Sikuati area with the structural and petroleum system of Kudat Peninsula. The abundance of highly carbonaceous rocks with presence of lamination in the Sikuati Member outcrop at Kudat Peninsula may give an idea on the presence of oil seepage in this area. A detailed geochemical analysis of source rock sample and oil seepage from Sikuati area was carried out for their characterization and correlation. Hydrocarbon propectivity of Sikuati Member source rock is poor to good with Total Organic Carbon (TOC) value of 0.11 to 1.48. and also categorized as immature to early mature oil window with Vitrinite Reflectance (VRo) value of 0.43 to 0.50 Ro. Based on biomarker distribution, from Gas Chromatography (GC) and Gas Chromatography-Mass Spectrometry (GC-MS) analysis, source rock sample shows Pr/Ph, CPI and WI of 2.22 to 2.68, 2.17 to 2.19 and 2.46 to 2.74 respectively indicates the source rock is immature and coming from terrestrial environment. The source rock might be rich in carbonaceous material organic matter resulting from planktonic/bacterial activity which occurs at fluvial to fluvio-deltaic environment. Overall, the source rock from outcrop level of Kudat Peninsula is moderately prolific in term of prospectivity and maturity. However, as go far deeper beneath the surface, we can expect more activity of mature source rock that generate and expulse hydrocarbon from the subsurface then migrating through deep-seated fault beneath the Sikuati area. © Published under licence by IOP Publishing Ltd.